PENGARUH PENGAWASAN TERHADAP DISIPLIN KERJA PEGAWAI DI DINAS PERUMAHAN KAWASAN PEMUKIMAN DAN PERTANAHAN KABUPATEN CIREBON: The Influence of Supervision on Employee Work Discipline at the Office of Housing, Settlement Areas, and Land Affairs of Cirebon Regency - Heru Purwanto; Erna Erna; Ade Setaidi (Jurnal Investasi, 2025)
This study aims to analyze the influence of supervision on employee work discipline at the Cirebon Regency Housing, Residential Areas, and Land Agency. Supervision is understood as an organizational control mechanism that includes direct and indirect supervision, while work discipline includes preventive and corrective discipline. The study used a quantitative approach with a saturated sampling technique with all 79 employees as respondents. Data were collected through questionnaires and analyzed using descriptive statistics and path analysis. The results showed that supervision was in the "good" category with an average value of 3.70, while work discipline showed an average value of 3.85. The path analysis showed that supervision had a positive and significant influence on employee work discipline. These results confirm that strengthening supervision—both direct and indirect—plays an important role in improving employee work discipline. These findings contribute to the development of internal supervision policies in regional apparatus organizations.